Internet communities - R. V. Bolgov (Vestnik MGIMO-Universiteta)
This paper attempts to answer the question of whether the Internet community and the individual users of social networks are actors in world politics. They are gaining political influence, and Web 2.0 technologies are increasingly political. We analyze projects integrating social web services to interact with government information systems by citizens, NGOs and business are analyzed. We identify basic advantages and limitations of using social Internet services in politics. We examine experience of their use in government agencies in several countries. We analyze official documents governing the use of social networks in the interaction of authorities with the citizens and business